Toxicology of milrinone by zebrafish embryotoxicity test: Zebrafish embryotoxicity of milrinone - Li, Lingfeng; Chen, Zhen; Zheng, Zihe; Dai, Xiaofu (Cellular and Molecular Biology, 2024)
Milrinone, a phosphodiesterase III inhibitor with contractile and vasodilatory effects, is widely used in acute decompensated heart failure and medically refractory end-stage heart failure (HF). The adverse reactions of milrinone have been extensively explored clinically, but its possible toxicities and underlying molecular mechanisms in embryo development need further understanding as its clinical applications increase. Herein, we assessed the milrinone toxicity using the zebrafish embryotoxicity test (ZET), with a view of providing evidence and guidance for gravidas medicine. We carried out ZET by exposing embryos to a milrinone culture with a series concentration gradients since 1.5 hours post fertilization (hpf) and observed and assessed mortality and hatching rates of drug-treated zebrafishes at 24, 48, 72, and 96 hpf. No significant lethal effect was found in milrinone-treated zebrafish, but hatching rate of eggs at 48 hpf was up-regulated with the increase of milrinone concentration. The impact of milrinone on embryogenesis was assessed through body length, eye area, yolk sac area, swim bladder inflation area, pericardial area and venous congestion area at 96hpf. 150 μg/mL or higher milrinone treatment showed significant effects in the indicators. Organ disorders including enlarged pericardium, liver atrophy and decreased blood vessels were observed in dysplasia individuals versus controls. TUNEL assay suggested the ability of milrinone to induce apoptosis in malformation embryos. Quantitative real-time PCR showed aberrant expressions of transcription factors associated with heart development and genes related to liver development and apoptosis regulation. Therefore, ZET is feasible for the milrinone toxicity test, and high-dose milrinone causes harm to the embryonic development of zebrafish, especially in embryonic carcinogenesis, vasculogenesis, and hepatogenesis.